Simulation of Acoustic Behavior of Bubbly Liquids with Hybrid Lattice Boltzmann and Homogeneous Equilibrium Models (Communications in Computational Physics, 2018)
Homogeneous equilibrium model (HEM) has been widely used in cavitatingflow simulations. The major feature of this model is that a single equation of state(EOS) is proposed to describe the thermal behavior of bubbly liquid, where both kinematicand thermal equilibrium are assumed between two phases. In this paper, the HEMwas coupled with multi-relaxation-time lattice Boltzmann model (MRT-LBM) and theacoustic behavior was simulated. Two approaches were applied alternatively: adjustingspeed of sound (Buick, J. Phys. A, 2006, 39:13807-13815) and setting real gas EOS.Both approaches result in high accuracy in acoustic speed predictions for different void(gas) volume of fractions. It is demonstrated that LBM could be successfully appliedas a Navier-Stokes equation solver for industrial applications. However, further dissipationand dispersion analysis shows that Shan-Chen type approaches of LBM aredeficient, especially in large wave-number region.